The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.4081/rt.2016.6140
|View full text |Cite
|
Sign up to set email alerts
|

Langerhan's Cell Sarcoma: Two Case Reports

Abstract: Langerhan’s cell sarcoma (LCS) is a rare neoplasm with a poor prognosis. To our knowledge, only sixty-six cases have been published. We discuss two patients who presented very differently with LCS, as well as a recently published review of all sixty-six cases. Our first case had a complicated history of metastatic, high-grade myxofibrosarcomas and presented with a single skin lesion of LCS which was treated with resection to a positive margin and adjuvant radiotherapy. The LCS recurred locoregionally and was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…To our knowledge, characteristic chromosomal abnormalities or cytogenetic mutations are unknown in LCS. PET/CT is a good modality for staging and evaluating LCH, 7 and can be used to identify LCS lesions 8 . However, in this current case, the lesions were unevaluable by PET/CT.…”
Section: To the Editormentioning
confidence: 60%
See 1 more Smart Citation
“…To our knowledge, characteristic chromosomal abnormalities or cytogenetic mutations are unknown in LCS. PET/CT is a good modality for staging and evaluating LCH, 7 and can be used to identify LCS lesions 8 . However, in this current case, the lesions were unevaluable by PET/CT.…”
Section: To the Editormentioning
confidence: 60%
“…EPOCH chemotherapy has been reported to be highly effective for refractory or relapsed non-Hodgkin’s lymphoma 17 . Kaleem et al demonstrated that EPOCH was effective for an LCS patient with multi-organ lesions 8 . We speculate that EPOCH chemotherapy was highly effective due to a pathogenic similarity with Merkel cell carcinoma (MCC).…”
Section: To the Editormentioning
confidence: 84%
“…While CD1a and/or langerin are considered pathognomonic for LCH, they also stain positive in Langerhans cell sarcoma, an extremely rare disease with fewer than 100 cases reported. 19 Treatment of temporal bone LCH is dependent on the stage and severity of disease. 12 While no consensus treatment regimen is available, several treatment modalities have been proven effective.…”
Section: Discussionmentioning
confidence: 99%
“…While CD1a and/or langerin are considered pathognomonic for LCH, they also stain positive in Langerhans cell sarcoma, an extremely rare disease with fewer than 100 cases reported. 19 …”
Section: Discussionmentioning
confidence: 99%